2023
DOI: 10.1111/bcp.15691
|View full text |Cite
|
Sign up to set email alerts
|

A population pharmacokinetic model to guide clozapine dose selection, based on age, sex, ethnicity, body weight and smoking status

Abstract: AimsGuidance on clozapine dosing in treatment‐resistant schizophrenia is based largely on data from White young adult males. This study aimed to investigate the pharmacokinetic profiles of clozapine and N‐desmethylclozapine (norclozapine) across the age range, accounting for sex, ethnicity, smoking status and body weight.MethodsA population pharmacokinetic model, implemented in Monolix, that linked plasma clozapine and norclozapine via a metabolic rate constant, was used to analyse data from a clozapine therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…22 Model-based estimates from TDM data gave the half-lives of clozapine and of norclozapine as 36 and 69 hours, respectively (White European male, nonsmoker, 40 years, 70 kg). 23 The half-life of clozapine is shorter in smokers, in younger people, and in people of Afro-Caribbean ancestry, and longer in women, in older people, and in people of South Asian ancestry. Other factors, including diet, polymorphisms in genes coding for CYP450 enzymes, the presence of clozapine-induced gastrointestinal hypomotility, and certain coadministered drugs may also affect clozapine pharmacokinetics in individual patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Model-based estimates from TDM data gave the half-lives of clozapine and of norclozapine as 36 and 69 hours, respectively (White European male, nonsmoker, 40 years, 70 kg). 23 The half-life of clozapine is shorter in smokers, in younger people, and in people of Afro-Caribbean ancestry, and longer in women, in older people, and in people of South Asian ancestry. Other factors, including diet, polymorphisms in genes coding for CYP450 enzymes, the presence of clozapine-induced gastrointestinal hypomotility, and certain coadministered drugs may also affect clozapine pharmacokinetics in individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma half-life of clozapine has been reported as 9 to 17 hours, 21 but this increases after repeat dosing 22 . Model-based estimates from TDM data gave the half-lives of clozapine and of norclozapine as 36 and 69 hours, respectively (White European male, nonsmoker, 40 years, 70 kg) 23 . The half-life of clozapine is shorter in smokers, in younger people, and in people of Afro-Caribbean ancestry, and longer in women, in older people, and in people of South Asian ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…An olanzapine population pharmacokinetic model using the plasma olanzapine concentrations from the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) 15 demonstrated that African-Americans need higher doses (1.3 times higher) than Whites to reach the same olanzapine concentrations. The predicted need for higher clozapine concentrations in patients of African ancestry 16 to reach the minimum therapeutic dose had been verified by a population pharmacokinetic study from the United Kingdom that was published electronically on February 15, 2023 17 …”
mentioning
confidence: 93%
“…The predicted need for higher clozapine concentrations in patients of African ancestry 16 to reach the minimum therapeutic dose had been verified by a population pharmacokinetic study from the United Kingdom that was published electronically on February 15, 2023. 17…”
mentioning
confidence: 99%
“…Patients of Asian (of ancestries ranging from Pakistan to Japan) or American ancestry (indigenous or native Americans) require the lowest clozapine doses, whereas those of European ancestry require intermediate doses and those of African ancestry require the highest doses. 27,28 In adults with schizophrenia, the average minimum therapeutic dose required to reach a plasma or serum concentration of 350 ng/mL was used to compare individuals and groups based on clozapine clearance. The minimum therapeutic dose ranges are as follows: (1) 166 mg/d (nonsmoker women) to 270 mg/d (smoker men) in patients of Asian (or American) ancestry, (2) 236-368 mg/d in patients of European ancestry, (3) and 300-600 mg/d in patients of African ancestry (based on US recommended doses).…”
Section: Introductionmentioning
confidence: 99%